18F-FDG PET/CT metabolic parameter changes to assess vascular inflammatory response in patients with diffuse large B-cell lymphoma - Wenli Xie; Lixiu Cao; Jing Yu; Aijuan Tian; Jin Wang; Runlong Lin (BMC Medical Imaging)
Abstract Objective To study the changes in positron emission tomography with 2-deoxy-2-[fluorine-18]fluoro-D-glucose integrated with computed tomography (18F-FDG PET/CT) aortic target-to-background ratio (TBR) and aortic calcification scores before and after 6 cycles of chemotherapy with the rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) regimen in patients with diffuse large B-cell lymphoma (DLBCL). Patients and methods We selected 161 patients with DLBCL who received 6 cycles of R-CHOP standard chemotherapy and underwent baseline and 6-cycle efficacy evaluations using 18F-FDG PET/CT examinations at the Second Hospital of Dalian Medical University from July 2017 to June 2023. Additionally, 125 patients who underwent 18F-FDG PET/CT for physical examination during the same period, without active malignancy or systemic inflammatory disease, were chosen as the control group. We measured metabolic tumor volume (MTV) and total lesion glycolysis (TLG) of systemic lymphoma lesions in tumor patients. Aortic wall FDG uptake was semi quantitatively analyzed as TBR (target-to-blood pool ratio) in five different vascular regions using oncological 18F-FDG PET/CT. The aortic TBR difference (ΔTBR) was the difference between the post- and pre-chemotherapy TBR values. The degree of arterial segmental wall calcification was assessed using the CT semiquantitative method. Results Comparison of the pre-treatment group of DLBCL with the control group showed that aortic TBR (1.28 ± 0.17 vs. 1.22 ± 0.18, P < 0.05) were higher in the former group. Additionally, comparing different stage groups of patients with DLBCL revealed that aortic TBR (1.30 ± 0.18 vs. 1.22 ± 0.15, P < 0.05) were higher in the Stage III/IV group compared to the Stage I/II group. Aortic TBR was positively correlated with TLG (P = 0.016, R = 0.19) and MTV (P = 0.032, R = 0.17). Analysis of changes in aortic 18F-FDG uptake in patients with DLBCL after 6 cycles of treatment revealed that aortic TBR levels were significantly higher post-treatment compared to pre-treatment(P < 0.05). The aortic ΔTBR value was significantly higher in the progression group than in the complete remission group(P < 0.05). Conclusion Aortic wall 18F-FDG uptake is related to disease severity and prognosis, indicating a possible vascular effect of lymphoma and its therapeutic interventions. This work highlights an additional potential role of PET/CT in imaging oncology for evaluating disease severity and its consequences on the vasculature.